Risk and prognosis of myocardial infarction in patients with neurofibromatosis type 1: Evidence of compromised survival - Loponen, Niina; Kallionpää, Roope A.; Ylä-Outinen, Heli; Valtanen, Mikko; Auranen, Kari; Järveläinen, Hannu; Peltonen, Sirkku; Peltonen, Juha (Elsevier BV, 2026)
Purpose
To analyze the risk and prognosis of myocardial infarction in patients with neurofibromatosis type 1 (NF1) in a Finnish population-based cohort from 1987 to 2021.
Methods
A cohort of 1811 individuals with confirmed NF1 was compared with a control cohort of 18,006 individuals who were matched for sex, date of birth, and municipality. Diagnoses of myocardial infarction and potentially associated risk factors were retrieved from the Finnish Care Register for Health Care and the Causes of Death Register over the years 1987 to 2021.
Results
We observed 42 individuals with NF1 (19 women and 23 men) with myocardial infarction. The hazard ratio (HR) for all was 1.36 (95% CI 0.98-1.88); for women 1.58 (95% CI 0.97-2.57), and for men 1.24 (95% CI 0.81-1.91). The diagnoses preceding myocardial infarction in patients with NF1 did not differ from controls. Disease-specific 5-year survival after hospital admission for myocardial infarction was 69.2% (95% CI 54.8-87.6) in patients with NF1 and 85.0% (95% CI 81.0-89.2) in controls, corresponding to a significantly worse prognosis in the NF1 group (HR 2.22, 95% CI 1.16-4.24). NF1-related cancers and sleep apnea often occurred in association with deaths caused by myocardial infarction.
Conclusion
NF1 appears to be frequently associated with myocardial infarction and a subsequent significantly poor survival.